ANALISIS PROSES GAS FREEING PADA CARGO TANK LPG/C CORAL IVO-RY - Nezwanie Aulia; Achmad Ali Mashartanto; Rizal Rochmansyah; Edi Kurniawan; Arya Widiatmaja (STKIP Subang, 2026)
Gas carrier vessels have a high level of operational risk due to the characteristics of the cargo, which is volatile, pressurized, and can be toxic, such as ammonia. One of the important stages after cargo discharge is gas freeing, which is the process of removing residual gas vapour inside the cargo tank until it reaches a condition that is safe for entry. This process aims to ensure that the tank is free from hazardous gases so that it is safe for the crew to carry out maintenance or inspection activitiesThis study aims to determine the implementation process of gas freeing, identify the obstacles that occur, and analyze the efforts made to overcome these obstacles on LPG/C Coral Ivory. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using a fishbone diagram to identify the factors causing the problems. The results show that the obstacles in the gas freeing process are influenced by material, method, and measurement factors. The efforts to overcome these problems include optimizing the warming-up process, adjusting inerting and purging gradually, and improving gas monitoring to ensure that the tank condition meets safety procedures.